Transformation of the B2B services in Bangladesh: a study on the value addition created from the perspective of ShopUp - Alam, Mohammad Rafat (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.